PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PT. TELEKOMUNIKASI INDONESIA BERDASARKAN PENILAIAN INDONESIA INSTITUTE OF CORPORATE GOVERNANCE - AGUSTINA RAHAYU, ALVI Agustina (Jurnal Akuntansi AKUNESA, 2013)
This research will try to prove whether application of good corporategovernance will influence the finance performance. The finance performance ismeasured by Return of Equity (ROE) and Return of Asset (ROA) as the majorconsideration for investors and creditors to invest for the companies.Corporate governance application is measured by using CorporateGovernance Perception Index value of IICG survey results.Statistical methodused in this research is linier regression. Research sample is PT.Telekomunikasi Indonesia Tbk as 2010 the most trusted company. Based on thehypotheses test, the result shows that GCG do not influence corporate financeperformance.Keywords : Corporate Governance, Finance Performance, ROE, ROA, IICG,corporate governance perception index